Identifying obstacles is not enough for everybody—Differential efficacy of an intervention fostering fifth graders' comprehension for word problems. (March 2021) - Dröse, Jennifer; Prediger, Susanne
Highlights: Understanding word problems demands comprehension strategies and language awareness. Language-responsive interventions use variation principle and strategic scaffolding. Identifying obstacles is not enough for implementing effective teaching. Effective teaching needs teachers' professional development and curriculum support. Abstract: For students' success in treating word problems, language obstacles have been identified. Interventions are required for students to overcome them, likewise professional development and curriculum support for teachers. But how much support do teachers need? In a controlled trial evaluation study, two interventions for n = 275 fifth graders are compared: The language-responsive intervention (LRI) uses the variation principle and strategic scaffolding fostering comprehension strategies and language awareness. The information-problems-only intervention (IPI) uses the same set of word problems, but teachers were only informed about typical obstacles. For the evaluation study, the ANOVA shows that in both interventions, students have significantly more learning gains than in the no-treatment group, and substantially more in the LRI than in IPI. Students with different language backgrounds profit comparably from LRI, but in different subscales. In conclusion, identifying obstacles is not enough for implementing effective teaching, it should be enhanced by curriculum support.